2013
DOI: 10.1002/lary.24077
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the detection of locoregional recurrence in head and neck malignancies: F‐18 fluorodeoxyglucose–positron emission tomography/computed tomography compared to high‐resolution contrast‐enhanced computed tomography and endoscopic examination

Abstract: HRCT increases the specificity and PPV of PET/CT when acquired simultaneously with PET. FDG-PET/CT acquired with either LDCT or HRCT has higher accuracy than HRCT alone and increases the sensitivity and NPV of PE/E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Conversely, Sheikhbahaei et al did not find a substantial difference in the diagnostic performance of 18 F‐FDG PET or PET/CT before and after 12 weeks . Our current knowledge suggests that 18 F‐FDG PET/CT can rule out residual or recurrent disease better than anatomical imaging and physical exam . However, the timing of posttreatment 18 F‐FDG PET/CT should be balanced according to the clinical need for early diagnosis of disease relapse, salvage options, and prognostic information when management decisions arise.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, Sheikhbahaei et al did not find a substantial difference in the diagnostic performance of 18 F‐FDG PET or PET/CT before and after 12 weeks . Our current knowledge suggests that 18 F‐FDG PET/CT can rule out residual or recurrent disease better than anatomical imaging and physical exam . However, the timing of posttreatment 18 F‐FDG PET/CT should be balanced according to the clinical need for early diagnosis of disease relapse, salvage options, and prognostic information when management decisions arise.…”
Section: Discussionmentioning
confidence: 66%
“…They compared the recurrence detection rate of post treatment diagnostic HRCT, PET/CT (low dose CT) and PET/CT performed 18 months after treatment. Their results showed higher sensitivity respectively for PET/HRCT, PET/CT and HRCT in recurrence detection of their heterogenous patient population [14]. In addition, a few studies comparing the accuracy of these two modalities without accounting for the same day PET/CT and CECT scans have been reported [2427].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, dental repair materials, i.e. metal artifacts, may obscure the oropharyngeal area and decrease the value of CECT scan in the therapy assessment setting [14,15]. Considering all of these limitations, CECT still has a great value in management of patients with OPSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Delouya et al, it could be an additional tool to help radiation oncologists in target delineation. A few studies have already shown the interest to integrate 18 FDG PET‐CT into treatment response evaluation strategy, underlining the higher specificity and negative predictive value of 18 FDG PET‐CT compared to conventional imaging for posttreatment evaluation . Indeed, the size and aspect of the tumor after therapy are not directly related to the viability of the tumor.…”
Section: Introductionmentioning
confidence: 99%